New species, identification keys and notes on Lamiinae (Coleoptera, Cerambycidae) from the Neotropical region - Nascimento, Francisco E. De L. (Zootaxa, 2018)
Three new species of Neotropical Lamiinae are described and illustrated: Cleodoxus antonkozlovi, Hyperplatys pacangensis, and Drycothaea indivisa. The first identification key to species of Cleodoxus Thomson, 1864, and notes on all three genera are provided.